Analisis Pengaruh Kecepatan dan Waktu Pengadukan terhadap Homogenitas Sampah Organik dalam Proses Pengomposan - Dimas Vrisnanda Yulio Diva Prakasa; Haris Puspito Buwono (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
The problem of household waste, which accounts for 50-70% of the total waste in Indonesia, mainly in the form of organic waste such as food and vegetable scraps, is a major challenge in environmental management. Composting is an effective method of managing organic waste by turning it into compost. However, organic waste management in Indonesia is still minimally practiced because it is considered to have no economic value. A 50 kg capacity composter machine equipped with a vertical mixer and using an electric motor can increase composting efficiency. This study aims to analyze the feasibility of composter machines and to analyze the effect of speed and mixing time on composter machines on the homogeneity of organic waste. The research method used is quantitative experimental with factorial experimental design (DOE) to analyze the effect of speed and stirring time on the composter machine on the homogeneity of organic waste. The stirring speed variations tested were 30, 45, and 60 RPM, with mixing times of 20, 30, and 40 minutes. The results showed that the single mixer composter machine proved to be feasible and reliable in producing homogeneous organic waste, with a high process capability value of 5.86. The use of mixing speed from 30 RPM to 60 RPM and mixing time from 20 minutes to 40 minutes significantly increased the homogeneity of organic waste, with the highest value of 97.54% at 60 RPM speed for 40 minutes.